Policy frameworks supporting Africa–Europe STI cooperation: Past achievements and future responsibilities. - Barugahara, Ismail; Tostensen, Arne (Palgrave Macmillan, Cham., 2018)
This chapter provides an overview of the chronological developments of the Africa–Europe cooperation on science, technology and innovation (STI). The authors first remind readers that African–European cooperation bears the mark of the prior colonisation of the African continent and the deep establishment of unequal and (geographically) unbalanced cooperation patterns. They then reflect on the renewed interest in STI in Africa–Europe cooperation. The chapter explains how more balanced cooperation structures and more efficient financing systems can be achieved and how science can become an integrated part of global development strategies.
Keywords: Framework programme • Africa–Europe economic agreements • International cooperation strategy • Sustainable cooperation • Global development • STI cooperation